EFEK PEMBERIAN GULA KELAPA YANG DIPERKAYA MINYAK SAWIT MERAH TERHADAP PENINGKATAN BERAT BADAN DAN KADAR RETINOL SERUM TIKUS DEFISIEN VITAMIN A (EFFECT OF THE FEEDING OF BROWN SUGAR ENRICHED WITH RED PALM OIL ON BODY WEIGHT GAIN AND SERUM RETINOL LEVELS - Hidayah Dwiyanti; Hadi Riyadi; Rimbawan Rimbawan; Evy Damayanthi; Ahmad Sulaeman; Ekowati Handharyani (Persagi, 2013)
ABSTRACT Vitamin A deficiency (VAD) is an important cause of blindness and premature death. Vitamin A also plays an important role on growth and immune function. Red palm oil is the richest naturally occurring source of β-carotene, a carotenoid that the human body can convert into usable vitamin A (retinol). This research was to evaluate the effect of feeding red palm oil enriched brown sugar on improving body weight and serum retinol level of vitamin A depletion Sprague-Dawley rats. Twenty four of six weeks old-male Sprague Dawley rats were used. After 2 weeks of adaptation period, rats were given vitamin A deficient diet (modified AIN-93M) for 10 weeks, and then divided into 3 groups and received for 2 weeks the different treatment as repletion period: 1) RPO group which received red palm oil enriched brown sugar (1.5 mL/d), 2) CPO group which received crude palm oil enriched brown sugar (1.5 mL/d) and 3) and RE group which received retinyl palmitate (0.6 mL/d) . Each treatment contains approximately 40 µg beta carotene/day. Intervention by feeding brown sugar enriched with RPO and CPO for 2 weeks can increase the body weight of rats by 3.54 percent and 5.23 percent, respectively, which is markedly better than the group that was given retynil palmitat (9.38%) (p<0.05). However, an increase in serum retinol concentrations in all group showed no significant differences (p>0.05). Consumption of brown sugar enriched with RPO or CPO enhances body weight and serum retinol concentration of vitamin A deficient rats. Keywords: brown sugar, red palm oil, serum retinol, vitamin A deficiency, rats ABSTRAK Kurang vitamin A (KVA) merupakan penyebab utama kebutaan dan kematian dini. Vitamin A juga berperan pada perkembangan dan fungsi imun. Minyak sawit merah merupakan sumber β-karoten, dimana tubuh dapat merubahnya menjadi retinol. Tujuan penelitian untuk mengevaluasi efek pemberian gula kelapa yang diperkaya minyak sawit merah terhadap peningkatan berat badan dan kadar serum retinol tikus Sprague-Dawley defisien vitamin A. Digunakan 24 ekor tikus jantan usia 6 minggu. Setelah 2 minggu masa adaptasi, tikus diberi diet bebas vitamin A selama 10 minggu, selanjutnya dibagi menjadi 3 kelompok, yaitu 1) RPO, menerima larutan gula yang diperkaya dengan RPO (1,5 ml/hari), 2) CPO, menerima larutan gula yang diperkaya CPO (1,5 ml/hari)), dan 3) RE, yaitu kelompok yang mendapatkan retynil palmitat dalam minyak sebagai kelompok kontrol positif (0,6 ml/hari). Masing-masing perlakuan mengandung beta karoten setara 7 RE per hari. Intervensi selama 2 minggu dengan memberikan gula kelapa yang diperkaya RPO maupun CPO mampu meningkatkan berat badan tikus masing-masing 3,54 persen dan 5,23 persen yang secara nyata lebih baik dibandingkan kelompok yang diberi retynil palmitat (-9,38%) (p<0,05). Disisi lain, peningkatan konsentrasi serum retinol pada semua kelompok tidak menunjukkan perbedaan yang nyata (p>0,05). Konsumsi gula kelapa yang diperkaya RPO maupun CPO meningkatkan berat badan dan memperbaiki konsentrasi serum retinol tikus defisien vitamin A. [Penel Gizi Makan 2013, 36(1):73-81] Kata kunci: gula kelapa, sawit merah, retinol serum, defisiensi vitamin A, tikus